Adaptive management for coastal sanitation governance in Jakarta, Indonesia: Bridging community resilience and the 100-0-100 development - Sofiyah, Evi Siti; Suryawan, I Wayan Koko (Institut Teknologi Sepuluh Nopember, 2025)
Coastal urban areas in Indonesia, particularly in Jakarta, face complex sanitation challenges due to rapid urbanization, environmental vulnerability, and the persistence of informal settlements. While national programs like the 100-0-100 initiative and the KOTAKU (Kota Tanpa Kumuh) program aim to achieve universal sanitation access and slum eradication, implementation in flood-prone coastal zones remains constrained by rigid infrastructure models, fragmented governance, and limited community engagement. This study employs a narrative review approach to examine how principles of adaptive management can enhance the effectiveness, inclusiveness, and resilience of coastal sanitation systems. Drawing on literature from urban planning, environmental governance, and participatory development, the study synthesizes insights across five core dimensions of adaptive management: assets, flexibility, organization, learning, and agency. The resulting framework highlights the importance of leveraging local knowledge, enabling flexible planning and financing, promoting inter-agency collaboration, institutionalizing learning mechanisms, and strengthening community leadership. By aligning technical solutions with social realities and environmental dynamics, adaptive management offers a pathway to improve sanitation governance while supporting Indonesia’s broader sustainable development and climate adaptation goals. The study concludes with policy recommendations to integrate adaptive approaches into the design and evaluation of urban sanitation programs, ensuring that no community is left behind in the pursuit of inclusive and resilient urban futures.